The Obstetric and Neonatal Implications of a Low Value on the 50-g Glucose Screening Test - Ma, Kimberly K.; Mele, Lisa; Landon, Mark B.; Spong, Catherine Y.; Ramin, Susan M.; Casey, Brian; Wapner, Ronald J.; Varner, Michael W.; Rouse, Dwight J.; Thorp, John M., Jr.; Sciscione, Anthony; Catalano, Patrick; Harper, Margaret; Saade, George; Caritis, Steve N.; Sorokin, Yoram; Peaceman, Alan M.; null (American Journal of Perinatology, 2013)
Objective To assess the relationship between a low 50-g 1-hour glucose loading test (GLT) and maternal and neonatal outcomes in women without diabetes.Study Design This was a secondary analysis of a multicenter observational cohort from a randomized trial of treatment for mild gestational diabetes. Maternal and neonatal outcomes were compared between women with GLT values < 90 mg/dL and those with results 90 to 119 mg/dL.Results Of 436 enrolled women, 297 (68.1%) had a GLT result of 90 to 119 mg/dL and 139 (31.9%) had a result of < 90 mg/dL. There was a lower incidence of neonatal hypoglycemia in those with a GLT < 90 mg/dL (5.7% versus 16.5%, p = 0.006). Other outcomes were not associated with test results.Conclusion A GLT result < 90 mg/dL compared with 90 to 119 mg/dL is associated with a lower risk of neonatal hypoglycemia, but no other significant findings.
Keywords: low glucose screening test; neonatal hypoglycemia